Whose truth did prevail? an analysis of the daily broadsheets, The Philippine Star, in the context of MVP (Manny V. Pangilinan) group’s acquisition. - Tubije, Rogelio II Bustamante
The MVP (Manny Pangilinan) Group of Companies is among the country's top conglomerates, with substantial holdings across diverse strategic fields such as telecommunications, infrastructure, water and power distribution, mining and healthcare. Yet what makes the MVP Group so powerful is its acquisition of various media outlets, ranging from TV, radio to print media. This includes the Philippine Star - one of the country's top broadsheets. With the new ownership, Star was caught in a dilemma. Its parent conglomerate subsidiaries have been subject to controversies like overpricing and substandard services. Thus, it is important to determine if such corporate orientation runs afoul to the press's primary duty as watchdog of society.